2000
DOI: 10.1021/jp0000329
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Electron-Transfer Properties of Mono- and Multiple-Functionalized Fullerene Derivatives

Abstract: Mono-and multiple-functionalized C 60 derivatives were synthesized and studied for their photophysical properties. Electronic absorption spectra and absorptivities of the C 60 derivatives in solution were measured and compared. By recording the fluorescence spectra using a near-infrared-sensitive emission spectrometer, we quantitatively determined fluorescence quantum yields of the C 60 derivatives. For the mono-functionalized C 60 derivatives, the compound with a [5,6]-open fulleroid addition pattern on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 55 publications
(90 reference statements)
3
48
1
Order By: Relevance
“…The principal possibility of using a,b-dibromo derivatives of acid esters in the Bingel reaction was demonstrated by synthesizing methanofullerene 35 (Scheme 11). 35 In a search for highly water-soluble fullerene derivatives, condensation of equimolar amounts of a bromomalonodiamide derivative and C 60 gave adduct 36, 36 hydrolysis of which resulted in methanofullerene 37 (Scheme 12). However, neither tetraacetate 36 nor even tetraol 37 showed any noticeable water solubility.…”
Section: Synthesis Of Methanofullerenes Based On Halide-activated Submentioning
confidence: 99%
“…The principal possibility of using a,b-dibromo derivatives of acid esters in the Bingel reaction was demonstrated by synthesizing methanofullerene 35 (Scheme 11). 35 In a search for highly water-soluble fullerene derivatives, condensation of equimolar amounts of a bromomalonodiamide derivative and C 60 gave adduct 36, 36 hydrolysis of which resulted in methanofullerene 37 (Scheme 12). However, neither tetraacetate 36 nor even tetraol 37 showed any noticeable water solubility.…”
Section: Synthesis Of Methanofullerenes Based On Halide-activated Submentioning
confidence: 99%
“…Applications of such compounds are therefore not limited by their availability. In addition, hexa‐substituted fullerene derivatives are only weak electron acceptors34 and no longer efficient singlet oxygen sensitizers 35. Therefore, problems associated with the phototoxicity of mono‐ or di‐substituted fullerene derivatives36 resulting from the production of ROS are prevented in the case of hexasubstituted derivatives.…”
Section: From Glycofullerenes To Fullerene Sugar Ballsmentioning
confidence: 99%
“…This fact, however, does not mean necessarily that there is no emission from fullerene. In fact, it is well demonstrated that the quantum yield of fullerene derivatives is very low (17), and consequently it is reasonable to consider that the residual pyrene-OPV emission covers the fullerene one due to the difference in several orders of magnitude of the relative quantum yields (12). The fluorescence quantum yield of the pyrene OPV-aldehydes is around 30-40%.…”
Section: Optical Properties In Solutionmentioning
confidence: 99%